Kepemimpinan Profetik Era Post-Truth: Analisis Etika Komunikasi Islam dan Hiperkonektivitas - Ahmad Sofian; Ahmad Tamrin Sikumbang (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2026)
The main focus of this research is the shifting meaning of leadership in the post-truth era, where leaders' communication is often trapped in hyperreality and false imagery. This study aims to analyze the characteristics of Islamic leadership as an antithesis to the crisis of communication ethics in the digital era. Using library research, the data are examined through critical philosophical and thematic analysis of Islamic literature, contemporary communication theory, and post-truth discourse. The results show that prophetic characteristics (siddiq, amanah, tabligh, and fathonah) are not merely normative morality but ontological foundations in organizational and public communication. In the era of hyperconnectivity, Islamic leaders are required to deconstruct media simulacra by prioritizing tabayyun and qaulan sadida. Practically, these findings provide a conceptual basis for prophetic leadership literacy in Islamic organizations, educational institutions, and public policy settings so that public communication becomes more authentic, transparent, and resilient against digital misinformation.